Pengembangan Majalah Digital Berbasis Contextual Learning Sebagai Bahan Ajar Pada Materi Hakikat Ilmu Kimia Di MA Bustanul Muta’allimin Kota Blitar - Andika, Moh Andika Luqmanur Rizal (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
This study aims to develop a digital magazine based on contextual learning on the nature of chemistry. The research was conducted based on the importance of developing teaching materials that have criteria for attracting students' interest in the learning process. This type of research is research and development (R&D) using a 4D development flow modified to 3D. Eligibility criteria are known based on the results of validation tests and student response tests. The validation test was carried out by 4 validators, namely 2 material expert validators and 2 media expert validators to determine the level of validity of digital magazines. Furthermore, after the digital magazine was declared valid, a response test was carried out with 20 students of class X MA Bustanul Muta'allimin Blitar City to find out the student's response to the digital magazine. The results of the validation test of material experts and media experts received very valid criteria with consecutive average percentage values of 89.49% and 88.15%. The results of the response test of 20 students of class X MA Bustanul Muta'allimin Blitar City received very good criteria with an average percentage score of 84.47%.